Surtitling in theatrical play : a case study of Chinglish - Huang, Hui Wen (2019)
Theatre as a form of arts is gaining popularity in the world, and there has been wide interest in the field of translation in theatre. Translation in theatre manifests itself in different areas in theatrical arts, such as in the form of surtitles, or the dialogues or lyrics. Traditionally, research in surtitling largely revolved around the surtitling of opera, and less focus has been placed on surtitling of plays. This author of this research paper therefore aims to examine suitable strategies to be used in the translation and creation of surtitles for theatrical plays, through a case study of Chinglish by David Henry Hwang. The author also addresses technical issues of surtitling such as length and positioning of surtitles. The project adopts a qualitative research method, which includes a case selection and textual analysis of the case, before proceeding to translate the source text into surtitles. According to Reiss’s text type and communicative functions, the source text is largely expressive, and the translated outcome should achieve the same function. After the translation, the translated surtitles are subjected to the author’s analysis with regards to the translation techniques used and its suitability in each context. Analysis of the translation suggests that when translating Chinglish into surtitles, phrases or utterances that consists of Chinese characteristics can be translated literally into Chinese and meaning would not be lost. For western culture-specific phrases, when translating into Chinese, free translation should be applied to accurately convey the intended meaning to the audience. Despite an in-depth discussion of the translation strategies used in project, potential limitations, such as a lack of generalizability and the tendency for subjective decision making, still exist.